Money Laundering in Canada : Chasing Dirty and Dangerous Dollars - Beare, Margaret E. (Book collections on Project MUSE., 2007)
"This new work by Margaret E. Beare and Stephen Schneider brings empirical evidence to the study of money laundering in Canada. The authors challenge the dominant, seemingly common-sense notion, fuelled by political posturing and policing rhetoric, that taking the profits away from criminals (proceeds of crime enforcement) is a rational and effective tactic. Using extensive research involving records gathered from police, financial institutions, and legal sources, the authors paint a picture of a dubious enforcement strategy beset by conflicting interests and agendas, an overly ambitious set of expectations, and reliance on an ambiguous body of evidence as to the strategy's overall merits."--Jacket